Features of the formation of immune layers of the population to SARS-CoV-2 in the Kharkov region for the period May-November 2020. Vaccination strategies. - Kuchma, Maksim; Volianskyi, Andrii; Yudin , Igor; Davydova, Tetiana; Kuchma, Iryna (Annals of Mechnikov's Institute, 2021)
The variability of infectious diseases leads to the fact that people are repeatedly exposed to new diseases that can pose a significant threat to life and health, put significant pressure on health care systems and affect the economic situation in the world. Imperfect methods of specific prevention and treatment at the present stage can not affect the spread of infection and localize the epidemic process. Today, the most relevant is the latest outbreak of coronavirus infection, which began in December 2019 in Wuhan (China) where a new pathogenic coronavirus SARS-CoV-2 was first detected. DOI: 10.5281/zenodo.5499657